2019
DOI: 10.17509/ijal.v9i2.20231
|View full text |Cite
|
Sign up to set email alerts
|

Recontextualisation of genre-based pedagogy: The case of Indonesian EFL classrooms

Abstract: Genre-based pedagogy has been adapted to the Indonesian national curriculum for subject English since 2004. There has been reports of its success and it now remains as an important part of the language curriculum at schools. However, there is a couple of considerations need to be taken seriously in relation with genre-based adaptation. First, genre-based pedagogy, based on systemic functional linguistics (SFL) theory, was developed in Australia in English as a mother tongue and ESL classrooms. Indonesian class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
1
13
0
1
Order By: Relevance
“…Other findings indicated that the genre-based pedagogy in Indonesian EFL classrooms had been recontextualized only in parts. If the genre-based pedagogy is not recontextualized appropriately, it may weaken the attainability of genre pedagogy's main goal, which is to uphold social justice through equal distribution of knowledge (Kartika-Ningsih & Gunawan, 2019). The limitation of the textbook used in is possibly one of the factors which lead to this partial recontextualization.…”
Section: Figurementioning
confidence: 99%
“…Other findings indicated that the genre-based pedagogy in Indonesian EFL classrooms had been recontextualized only in parts. If the genre-based pedagogy is not recontextualized appropriately, it may weaken the attainability of genre pedagogy's main goal, which is to uphold social justice through equal distribution of knowledge (Kartika-Ningsih & Gunawan, 2019). The limitation of the textbook used in is possibly one of the factors which lead to this partial recontextualization.…”
Section: Figurementioning
confidence: 99%
“…Despite the inclusion of genre-based pedagogy in the national curriculum for teaching English in lower and upper secondary school, most studies related to the implementation of genre-based pedagogy were reported to be conducted in tertiary level of education (Aunurrahman, Hamied & Emilia, 2017;Emilia & Fuad, 2015;Hariyanto, 2001). Very limited, if not any, studies have been conducted in secondary school, such as Pujianto, Emilia and Ihrom (2014) and Kartika-Ningsih and Gunawan (2019). Pujianto et al (2014) reported that the implementation of genre-based pedagogy would help students write a text, e.g.…”
Section: Genre-based Pedagogy In Indonesiamentioning
confidence: 99%
“…Therefore, the implementation of genre-based pedagogy in teaching writing has an important role in improving students' writing skills which students can produce texts in various genres of the text properly. Several studies on genre-based pedagogy in teaching writing as Kartika-Ningsih and Gunawan (2019), Pujianto, Emilia, and Ihrom (2014), Rozimela (2013), Nurlaelawati and Novianti (2017) proved that genre-based pedagogy can improve students' writing skills which students can produce texts in various genres appropriately. Through these various text models, students will enrich their knowledge of a text and produce it according to the type of text that they want, especially at the modelling, joint construction, and independent construction stages (Pujianto, Emilia, & Ihrom, 2014).…”
Section: Introductionmentioning
confidence: 99%